ZIF-67-derived ultrathin Co-Ni layered double hydroxides wrapped on 3D g-C3N4 with enhanced visible-light photocatalytic performance for greenhouse gas CO2 reduction. Issue 4 (August 2022) - Wang, Yanan; Li, Chenlu; Wan, Shipeng; Zhang, Cheng; Li, Zhongyu; Zhang, Shule; Zhong, Qin
Abstract: CO2 photoreduction into high value-added chemicals shows great application prospects in the fields of environmental protection and renewable energy. However, the design and preparation of new heterogeneous photocatalysts with efficient CO2 photoreduction activity remains a challenge. Here, hierarchical cobalt-nickel layered double hydroxides (CNLDH) were confined on the surface of 3D gC3 N4 (NCN) to construct the CNLDH-NCN hybrids for photocatalytic reduction of CO2 . The fabrication involves NaCl-template-assisted calcination, in-situ growth and in-situ etching. The CNLDH-NCN hybrids show a well-defined hierarchical and multi-hole structure, which promote the light-harvesting, charge separation and the adsorption of CO2 . The optimal hybrids show high photocatalytic performance of CO2 to CO (27.67 μmol∙g -1 ∙h -1 ), which is 6.0-fold and 3.6-fold of NCN and CNLDH, respectively. The novel strategy successfully integrates hierarchical CNLDHs and NCN into a spatial conductive network frame with homogeneous and intimate interfacial contacts, boosting the photocatalytic performance. Meanwhile, it provides a new insight for the construction of a promising catalyst for solar energy conversion. Graphical Abstract: ga1 Highlights: A versatile design and fabrication were demonstrated to synthesize hierarchical CNLDH-wrapped gC3 N4 . The cyano groups (CN) were introduced into g-C3 N4 as active sites to anchored Co-ZIF or CNLDH. Co-ZIF as self-template are in-situ etched by ion-exchange to obtain defective and hierarchical CNLDH; The conjugated structure between Co-ZIF and NCN is substituted by the hydrogen bonding effect between CNLDH and NCN. Benefiting from the unique structure and intimate interaction, the heterostructures show high photocatalytic performance and selectivity of CO2 to CO.